Electrodeposited copper foil with uniform matt surface

By adding nitrogen-containing cationic polymers to the electrolytic solution of electrodeposited copper foil and controlling the current density, combined with polishing treatment, the problem of uneven surface of copper foil under high current density is solved, uniform surface deposition and high production rate are achieved, and the reliability of automotive PCB is improved.

CN119506985APending Publication Date: 2025-02-25DUPONT ELECTRONICS INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411166842.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-25
Filing Date
2024-08-23
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

When existing electrodeposited copper foils are deposited at high current density, uneven light-dust surfaces are easily formed, resulting in poor etching and potential short circuit problems in automotive PCBs.

Method used

Electrodeposition copper foil with a uniform light-free surface was prepared by adding an appropriate amount of nitrogen-containing cationic polymer to the electrolytic solution and controlling the current density between 30 A/dm2 and 100 A/dm2 during the electrodeposition process, and combining polishing to planarize the protrusions.

Benefits of technology

The matte surface uniformity of the copper foil deposited under high current density is achieved, the formation of abnormal protrusions is reduced, the thickness and production rate of the copper foil are improved, and the reliability and safety of the automotive PCB are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506985A_ABST
    Figure CN119506985A_ABST
Patent Text Reader

Abstract

Disclosed is an electrodeposited copper foil having a uniform matt surface, having an average thickness of about 30 [mu] m to about 400 [mu] m, and having a matt surface and a glossy surface, in which the matt surface includes a plurality of protrusions; the number (PA50 +) of the protrusions on the matt surface having a planarization peak after polishing, having a surface area of 50 [mu] m2 or more per 1 mm2 of the matt surface, is 8.0 or less; the peaks of some of the protrusions on the matt surface are planarized by a) placing the electrodeposited copper foil on a glass substrate, where the matt surface is in contact with the glass substrate, and b) polishing away the glossy surface of the electrodeposited copper foil by using silicon carbide abrasive paper having a 1200 sand grain size. Methods for making the inventive electrodeposited copper foils and articles made therefrom are also disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electrodeposited thick copper foil having a uniform matte surface. The present invention also relates to a method for making the electrodeposited copper foil of the present invention and articles made therefrom. Background Art

[0002] Electronic systems used in vehicles include engine management systems, ignition systems, carputers, telematics, in-car entertainment systems, and other systems. Electronic systems have become an increasingly large component of automotive costs. Therefore, the demand for automotive PCBs used in the above electronic systems has increased significantly.

[0003] Compared to traditional consumer electronics, automotive PCBs must meet high reliability and safety standards. More specifically, copper foil suitable for automotive PCBs should have the following three characteristics: (1) have sufficient thickness to withstand high operating currents and allow good heat dissipation; (2) have a uniform matte surface to avoid undesirable etching during the manufacturing process and / or short circuits under operating conditions; and (3) allow for manufacturing at industrial production rates.

[0004] At a given current density, the thickness of the electrodeposited copper foil (hereinafter referred to as ED copper foil) is proportional to the electrodeposition duration. To have a thick ED copper foil without reducing the production rate, it is possible to deposit the copper foil at a higher current density (i.e., above 30 A / dm 2 ) is achieved by electrodeposition. However, the uniformity of the matte surface of the copper foil generally decreases as the current density increases. At high current density, copper crystals may be deposited unevenly at certain locations, forming abnormal protrusions (particularly high and large) on the deposited surface of the ED copper foil, and thus reducing the uniformity of the surface. Figure 1 A shows an SEM image of an ED copper foil having an abnormal protrusion among multiple protrusions on a matte surface. In contrast, Figure 1 B shows a SEM image of an ED copper foil with a uniform matte surface containing many protrusions of similar height and size. Figure 1 The uniform surface of the ED copper foil shown in B is ideal for application in automotive PCBs.

[0005] Generally, when the thickness of the copper foil is less than 30 μm, applying a high current density during electrodeposition may not cause serious uniformity problems on the matte surface (i.e., deposition surface) of the ED copper foil, because the electrodeposition duration is relatively short and there is not enough time to grow abnormal protrusions. However, when the electrodeposition duration is extended to manufacture a thick copper foil, it is expected that many abnormal protrusions will be formed on the matte surface of the ED foil. Therefore, a PCB made of a thick copper foil with poor uniformity may suffer from poor etching during the circuit formation stage and encounter potential short circuit problems when working later.

[0006] In order to minimize the formation of abnormal protrusions on the matte surface of ED copper foil, known solutions include: (1) reducing the current density used for electrodeposition; and (2) adding a large amount of conventional additives to the electrolytic solution. The main disadvantage of the first solution is that the production rate of copper foil decreases as the current density decreases. In addition, although the first solution may suppress the size and number of abnormal protrusions, it cannot prevent the formation of abnormal protrusions.

[0007] The second solution is to add conventional additives to provide a uniform copper foil surface under high current density conditions. However, large amounts of conventional additives in an electrodeposition bath reduce the useful life of the electrolytic solution and require additional removal steps when the electrolytic solution is disposed of as waste. In addition, it is difficult to control the quality of the copper foil during a continuous production process (i.e., a continuous production process performed by replenishing fresh electrolytic solution into an electrodeposition bath containing large amounts of conventional additives).

[0008] In view of the above, there is a need to develop an electrodeposited copper foil having a uniform matte surface to bring benefits to the printed circuit board industry in general, and to automotive PCBs in particular. Summary of the invention

[0009] In order to solve the above problems, the present invention provides an electrodeposited copper foil having a uniform matte surface and a method for manufacturing the electrodeposited copper foil.

[0010] According to a first aspect of the present invention, there is provided an electrodeposited copper foil having a uniform matte surface.

[0011] The electrodeposited copper foil has an average thickness (T 平均 ); the electrodeposited copper foil having a matte surface and a glossy surface; the matte surface of the copper foil comprises a plurality of protrusions; and each 1mm 2 The matte surface has a 50 μm 2 The number of protrusions on the matte surface having flattened peaks after polishing of a surface area of ​​or greater (PA 50+) is 8.0 or less; wherein the average thickness is measured by a scanning electron microscope (SEM); peaks of some protrusions on the matte surface are flattened by: a) placing the electrodeposited copper foil on a glass substrate, wherein the matte surface is in contact with the glass substrate, and b) polishing away about 1 μm of the glossy surface of the electrodeposited copper foil by using silicon carbide sandpaper with a grit size of 1200; the number and surface area of ​​the protrusions on the matte surface having flattened peaks after polishing are counted and measured by using an optical microscope with a magnification of 50 times or more and a resolution of at least 0.1 μm.

[0012] According to a second aspect of the present invention, a method for manufacturing the above-mentioned electrodeposited copper foil is provided. The method comprises:

[0013] i) providing an electrolytic solution in an electrolytic cell;

[0014] ii) applying a current of a certain current density to the anode plate and the rotating cathode electrode drum spaced apart from each other in the electrolytic solution;

[0015] iii) electrodepositing copper foil on the rotating cathode drum; and

[0016] iv) separating the copper foil formed in step iii) to obtain an electrodeposited copper foil;

[0017] in,

[0018] The electrodeposited copper foil has an average thickness of about 30 μm to about 400 μm;

[0019] The electrodeposition in step iii) is carried out at about 30 A / dm 2 To about 100A / dm 2 The current density is 2.14V.

[0020] The electrolytic solution comprises:

[0021] From about 120 g / L to about 450 g / L of copper sulfate;

[0022] From about 30 g / L to about 140 g / L of sulfuric acid;

[0023] From about 0.1 ppm to about 60 ppm of chloride ion; and

[0024] From about 0.1 ppm to about 50 ppm of additives.

[0025] According to a third aspect of the present invention, a surface-treated electrodeposited copper foil includes or is made of the electrodeposited copper foil of the present invention.

[0026] According to a fourth aspect of the present invention, there is provided a product, which comprises or is made of the electrodeposited copper foil of the present invention.

[0027] In one embodiment, the article includes a negative electrode collector of a lithium-ion battery, a copper-clad laminate, a flexible copper-clad laminate, a heat sink or a printed circuit board. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 SEM images of two copper foil specimens are shown. Figure 1 A is the matte surface of the copper foil sample of Comparative Example 3 (CE3), which has abnormal protrusions. Figure 1 B is the matte surface of the copper foil sample of Example 9 (E9), which has no abnormal protrusions and has high uniformity.

[0029] Figure 2 Shown are cross-sectional views of two surface treated electrodeposited copper foils according to embodiments of the present invention.

[0030] Figure 3 SEM photographs showing cross-sectional views of two copper foil specimens. Figure 3 A is a photograph of the copper foil sample of Comparative Example 3 (CE3), and Figure 3 B is a photograph of the copper foil sample of Example 9 (E9). DETAILED DESCRIPTION

[0031] Unless otherwise indicated, all publications, patent applications, patents, and other references mentioned herein are expressly incorporated by reference in their entirety for all purposes as if fully set forth.

[0032] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. In case of conflict, the present specification, including definitions, will control.

[0033] Unless otherwise indicated, all percentages, parts, ratios, etc. are by weight.

[0034] As used herein, the term "resulting from" is synonymous with "comprising." As used herein, the terms "comprises," "comprising," "includes," "including," "has," "having," "contain," or "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises a list of elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0035] The transitional phrase "consisting of" excludes any element, step, or ingredient not specified. If in a claim, such a phrase will render the claim closed-ended so that it does not include materials other than those described, except for impurities normally associated therewith. When the phrase "consisting of" appears in a clause in the body of a claim, rather than immediately following the preamble, it is limited only to the elements set forth in that clause; other elements are not excluded from the claim as a whole.

[0036] The transitional phrase "consisting essentially of is used to qualify a composition, method, or apparatus that includes materials, steps, features, components, or elements in addition to those literally discussed, provided that these additional materials, steps, features, components, or elements do not materially affect the basic and novel characteristics of the claimed invention. The term "consisting essentially of" is intermediate between "comprising" and "consisting of."

[0037] The term "comprising" is intended to include embodiments encompassed by the terms "consisting essentially of and "consisting of. Similarly, the term "consisting essentially of is intended to include embodiments encompassed by the term "consisting of.

[0038] When an amount, concentration, or other value or parameter is given as a range, a preferred range, or a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any upper range limit or preferred value with any lower range limit or preferred value, regardless of whether the range is disclosed separately. For example, when listing a range of "1 to 5", the listed range should be interpreted as including ranges such as "1 to 4", "1 to 3", "1-2", "1-2 and 4-5", "1-3 and 5". When a numerical range is listed herein, unless otherwise stated, the range is intended to include its endpoints, as well as all integers and fractions within the range.

[0039] When the term "about" is used in describing a value or an end-point of a range, the disclosure should be understood to include the specific value or end-point referred to.

[0040] In addition, unless expressly stated to the contrary, "or" refers to an inclusive "or" and not to an exclusive "or". For example, the condition A "or" B is satisfied by any of the following: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist).

[0041] As used herein, the term "hydrocarbyl" refers to an organic compound having at least one carbon atom and at least one hydrogen atom, which is optionally substituted with one or more substituents where indicated. "Alkyl" refers to a straight or branched saturated hydrocarbon having a specified number of carbon atoms and having a valence of one, such as methyl, ethyl, n-propyl, isopropyl, or different butyl, pentenyl, and hexenyl isomers. "Alkylene" refers to an alkyl having a valence of two. "Cycloalkyl" refers to a monovalent group having one or more saturated rings in which all ring members are carbon, such as cyclopropyl, cyclobutyl, cyclopentyl, and cyclohexyl; "cycloalkylene" refers to a cycloalkyl having a valence of two. Examples of "cycloalkylene" include cyclopropylene, cyclobutylene, cyclopentylene, and cyclohexylene. "Aryl" refers to a monovalent aromatic monocyclic or polycyclic ring system in which the ring members consist of carbon atoms and may include groups having an aromatic ring fused to at least one cycloalkyl or heterocycloalkyl ring, such as phenyl, biphenyl, triphenyl, naphthyl, and binaphthyl. "Arylene" refers to an aryl group having a valence of two. The total number of carbon atoms in a substituent is indicated by the "Ci-Cj" prefix.

[0042] The term "optionally substituted" is used interchangeably with the words "substituted or unsubstituted" or with the term "(un)substituted". The expression "optionally substituted with 1 to 4 substituents" means that there are no substituents (i.e., unsubstituted) or there are 1, 2, 3 or 4 substituents (limited by available bond positions). Unless otherwise indicated, an optionally substituted group may have one substituent at each substitutable position of the group, and each substituent is independently selected. "Halide" refers to fluoride, chloride, bromide and iodide.

[0043] The embodiments of the present invention as described in the Summary of the Invention include any other embodiments described herein, may be combined in any manner, and the descriptions of variables in the embodiments relate not only to the composite laminate of the present invention, but also to articles made therefrom.

[0044] The present invention is described in detail below.

[0045] The present invention relates to an electrodeposited copper foil having a uniform matte surface. Electrodeposited (ED) copper foil is manufactured by electrodeposition. Each ED copper foil has two surfaces; the surface facing the electrolytic solution during the manufacturing process is called the "deposition surface", and the opposite surface that contacts the cathode drum / roller is called the "drum surface" or "roller surface". Both surfaces of the ED copper foil have a distinguishable appearance, so the deposition surface is also called the matte surface, and the drum surface is called the glossy surface. When observed with a microscope with high magnification, the matte surface of the ED copper foil contains multiple protrusions. Due to uneven copper deposition, some protrusions are abnormally higher and larger than other protrusions. In general, the uniformity of the matte surface of the ED copper foil may be affected by the number and size of abnormally higher and larger protrusions per unit area of ​​the copper foil. As previously mentioned, when under high current density, such as at about 30A / dm 2 The phenomenon of non-uniform copper deposition is particularly prominent when electrodeposition is performed at 1000 Å or higher. Therefore, it is known that ED copper foils conventionally produced at high current density have poor uniformity on the matte surface.

[0046] The abnormally higher and larger protrusions on the matte surface of the ED copper foil can be revealed by a) placing the electrodeposited copper foil on a glass substrate with the matte surface in contact with the glass substrate, and b) polishing away about 1 μm of the shiny surface of the electrodeposited copper foil by using silicon carbide sandpaper with a grit size of 1200. Afterwards, the peaks of these abnormally higher and larger protrusions are flattened.

[0047] The surface area of ​​each protrusion having a flattened peak after the above-mentioned polishing can be observed and measured by a scanning electron microscope (SEM). Figure 1 A shows a SEM photograph of an ED copper foil sample (i.e., CE3) produced by electrodeposition in an electrolytic solution containing conventional additives, and the matte surface of the ED copper foil sample contains a plurality of protrusions. After polishing, there is an abnormally higher and larger protrusion with a flattened surface among the protrusions.

[0048] Generally speaking, for a 50μm 2 Abnormally higher and larger protrusions with flattened peaks after polishing of a surface area of ​​50 or more are counted because these protrusions significantly affect the uniformity of the matte surface of the ED copper foil. An optical microscope with a magnification of 50 times or more and a resolution of at least 0.1 μm is used to observe and count protrusions with a surface area of ​​50 μm or more. 2 or greater surface area after polishing with flattened peaks, and the number is determined by PA 50+ Because the size of the observation window of an optical microscope may vary depending on the instrument, every 1mm2 The number of protrusions on the matte surface (PA 50+ ) is used as an indicator of the uniformity of the matte surface of ED copper foil.

[0049] In addition, the uniformity of the matte surface of ED copper foil can be characterized by the uniformity factor (UF), which is calculated by Equation 1:

[0050] UF=A 最大 / T 平均 (Equation 1)

[0051] in

[0052] A 最大 : the maximum surface area of ​​protrusions on the matte surface having flattened peaks after polishing; and

[0053] T 平均 :Average thickness of ED copper foil (T 平均 ).

[0054] The electrodeposited copper foil having a uniform matte surface of the present invention has the following characteristics: (1) having an average thickness (T 平均 ); and (2) having a PA of 8.0 or less 50+ / 1mm 2 Matte surface.

[0055] The electrodeposited copper foil of the present invention further has a fourth feature that the matte surface of the electrodeposited copper foil has a uniformity factor (UF) of 5.5 μm or less.

[0056] In some embodiments of the present invention, PA 50+ / 1mm 2 The matte surface is about 7.0 or less, about 6.0 or less, about 5.0 or less, or about 4.0 or less, 3.0 or less, or about 2.0 or less.

[0057] In some embodiments of the present invention, the matte surface of the electrodeposited copper foil has a UF of 4.5 μm or less, or 3.5 μm or less, or 2.5 μm or less.

[0058] A second aspect of the present invention is to provide a method for producing the above-mentioned electrodeposited copper foil having a uniform matte surface, the method comprising the following steps:

[0059] i) providing an electrolytic solution in an electrolytic cell;

[0060] ii) applying a current of a certain current density to an anode plate and a rotating cathode drum spaced apart from each other in the electrolytic solution;

[0061] iii) electrodepositing copper foil on the rotating cathode drum; and

[0062] iv) separating the copper foil formed in step iii) to obtain an electrodeposited copper foil;

[0063] in

[0064] The electrodeposited copper foil has an average thickness of about 30 μm to about 400 μm;

[0065] The electrodeposition in step iii) is carried out at about 30 A / dm 2 To about 100A / dm 2 The current density is 2.14V.

[0066] The electrolytic solution comprises:

[0067] From about 120 g / L to about 450 g / L of copper sulfate;

[0068] From about 30 g / L to about 140 g / L of sulfuric acid;

[0069] From about 0.1 ppm to about 60 ppm of chloride ion; and

[0070] From about 0.1 ppm to about 50 ppm of additives.

[0071] In the method of the present invention, the electrolytic solution comprises copper sulfate, sulfuric acid, chloride ions, and additives. Copper sulfate is a source of copper ions, and sulfuric acid is an electrolyte in the electrolytic solution. Both copper sulfate and sulfuric acid can be commercially obtained from a variety of sources and used without further purification.

[0072] In some embodiments of the present invention, the amount of copper sulfate in the electrolytic solution is about 120 g / L to about 450 g / L; or about 180 g / L to about 400 g / L; or about 240 g / L to about 350 g / L, based on the total volume of the electrolytic solution.

[0073] In some embodiments of the present invention, the amount of sulfuric acid in the electrolytic solution is about 30 g / L to about 140 g / L; or about 35 g / L to about 130 g / L; or about 40 g / L to about 120 g / L, based on the total volume of the electrolytic solution.

[0074] The chloride ion source may be cupric chloride or hydrochloric acid. Chloride ion sources are commercially available and used without further purification.

[0075] In some embodiments of the present invention, the amount of chloride ions in the electrolytic solution is from about 0.1 ppm to about 60.0 ppm, or from about 1.0 ppm to about 55.0 ppm, or from about 2.5 ppm to about 50.0 ppm, or from about 5.0 ppm to about 45.0 ppm, or from about 10.0 ppm to about 40.0 ppm, based on the total weight of the electrolytic solution.

[0076] There is no specific limitation on the additives used in the present invention, as long as the electrodeposited copper foil prepared by the method of the present invention has a uniform matte surface. Additives suitable for the electrolytic solution include gelatin, animal glue, cellulose, organic sulfonic acid or its salt, nitrogen-containing cationic polymer, or a mixture thereof. Other additives such as accelerators, inhibitors, levelers or crystal orientation modifiers may also be added in combination of one or more types, depending on the specific application of the ED copper foil.

[0077] In some embodiments of the present invention, the additive comprises gelatin, animal glue, cellulose, organic sulfonic acid or its salt, nitrogen-containing cationic polymer, or a mixture thereof.

[0078] In the method for making the electrodeposited copper foil of the present invention, the amount of additive in the electrolytic solution depends on the specific additive selected, the concentration of copper ions, the concentration of sulfuric acid in the electrolytic solution, and the current density applied.

[0079] Since large-scale production operations of copper foil generally maintain the recycling of the electrolytic solution by replenishing the required components (e.g., copper ions, sulfuric acid, chloride ions, etc.), then filtering through a filter material to remove impurities and degraded one or more additives, and then pumping them into the electrolytic cell. When the total amount of the one or more additives is 50 ppm or less based on the total weight of the electrolytic solution, it is beneficial to reduce the use of filtering materials (such as activated carbon). Therefore, the method for making the electrodeposited copper foil of the present invention is beneficial for large-scale production and environmental protection.

[0080] In one embodiment of the present invention, the total amount of the one or more additives in the electrolytic solution is from about 0.1 ppm to about 50.0 ppm, or from about 0.5 ppm to about 40.0 ppm, or from about 1.0 ppm to about 30.0 ppm.

[0081] Known organic sulfonic acids or salts thereof suitable for use as brighteners or accelerators in the electrolytic solution include bis(sulfopropyl sodium) disulfide (SPS), sodium 3-(benzothiazolyl-2-mercapto)-1-propanesulfonate (ZPS), 3-S-thiourea propanesulfonate (UPS), sodium 3-mercapto-1-propanesulfonate (MPS), etc. The amount of the organic sulfonic acid or salt thereof in the electrolytic solution is generally in the range of 0.1 ppm to 20.0 ppm, or 0.5 ppm to 15.0 ppm, or 1.0 ppm to 10.0 ppm, based on the total weight of the electrolytic solution.

[0082] In one embodiment of the present invention, the additive is an organic sulfonic acid or a salt thereof.

[0083] Generally speaking, the nitrogen-containing cationic polymer (NCP) is the reaction product of an amine compound and an epoxy compound. Suitable amine compounds include, but are not limited to, dialkylamines, trialkylamines, arylalkylamines, diarylamines, imidazoles, triazoles, tetrazoles, benzimidazoles, benzotriazoles, piperidine, morpholine, piperazine, pyridine, oxazole, benzoxazole, pyrimidine, quinoline, isoquinoline, and the like. Preferably, the amine compound includes, but is not limited to, a diamine having formula (I) or an imidazole having formula (II):

[0084]

[0085] in

[0086] R 1 , R 2 , R 3 and R 4 are independently H or C1-C3 alkyl;

[0087] R 5 is H or C1-C6 alkyl;

[0088] R 6 , R 7 and R 8 Each of R is independently H or C1-C6 alkyl, and R 7 and R 8 optionally connected to each other to form a saturated ring;

[0089] A is a divalent linking group selected from the following: C2-C8 alkylene, C5-C 10 Cycloalkylene, phenylene and C6-C 20 Arylene, wherein A is optionally substituted with C1-C4 alkyl or OH; and

[0090] p, q and r are each independently an integer from 0 to 10.

[0091] Examples of diamines having formula (I) include, but are not limited to, ethylenediamine, tetramethyl-1,3-propylenediamine, N 1,N 4 -Diethyl-1,4-butanediamine, tetramethyl-1,5-pentanediamine, N 1 ,N 6 -dimethyl-1,6-hexanediamine, N,N,N',N'-tetramethyl-1,6-hexanediamine, 1,4-diaminocyclohexane, 1,4-cyclohexane-bis(methylamine), N,N,N',N'-tetramethyl-p-phenylenediamine, p-phenylenediamine, bis[2-(N,N-dimethylamino)ethyl]ether, bis(3-aminopropyl)ethane, 2,2'-[1,2-ethane-diylbis(oxy)]bis[N-methylethylamine, 1,1'-[1,2-ethanediylbis(oxy)]bis[2-propyl-amine], 1,2-bis(3-aminopropoxy)ethane, 3,3'-[oxybis(ethyleneoxy)]bis[N,N-dimethylpropylamine] and 3,3'-[oxybis(propyleneoxy)]bis[N,N-dimethylpropyl-amine].

[0092] Examples of imidazoles having formula (II) include, but are not limited to, 2H-imidazole, 2-methyl-imidazole, 4-methylimidazole, 2-ethylimidazole, 2-isopropyl-imidazole, and 2,5-dimethyl-1H-imidazole.

[0093] Suitable epoxy compounds include those having one epoxy group, diepoxides having two epoxy groups linked together by a bond, or polyepoxides having 3 or more epoxy groups. Preferably, these epoxy compounds include, but are not limited to, epoxides having formula (III) or diepoxides having formula (IV):

[0094]

[0095] in

[0096] Y is H or C1-C4 alkyl;

[0097] X is a halogen;

[0098] R 9 and R 10 are independently H or C1-C4 alkyl;

[0099] R 11 is selected from C2-C8 alkylene and C5-C 10 A divalent linking group of cycloalkylene, wherein R 11 is optionally substituted with C1-C4 alkyl or OH; and

[0100] n is an integer of 1 to 20.

[0101] Preferably, in the epoxide with formula (III), X is chlorine or bromine, and more preferably chlorine. When Y is C1-C4 alkyl, the alkyl can be unsubstituted or substituted, that is, one or more of its hydrogen can be replaced by another substituent group. The example of the compound with formula (III) includes but is not limited to epichlorohydrin and epibromohydrin.

[0102] Examples of diepoxides having formula (IV) include, but are not limited to, 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, triethylene glycol diglycidyl ether, 1,3-butanediol diglycidyl ether, glycerol 1,3-diglycidyl ether, neopentyl glycol diglycidyl ether, propylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, poly(propylene glycol) diglycidyl ether, 1,2-cyclohexanedimethanol diglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, poly(ethylene glycol) diglycidyl ether, and poly(polypropylene glycol) diglycidyl ether.

[0103] The preparation of the reaction product of an amine compound and an epoxy compound is well known, see, for example, U.S. Pat. No. 8,268,158, U.S. Pat. No. 7,662,981, U.S. Pat. No. 7,374,652, and U.S. Pat. No. 6,800,188. The reaction between the reaction product of an amine compound and an epoxy compound as described above can be carried out, for example, at a temperature of 30° C. to 90° C. for 45 minutes to 480 minutes. The reaction product typically has a molar ratio of the amine compound to the epoxy compound of 10:1 to 1:4, and more typically 2:1 to 1:2.

[0104] In one embodiment of the present invention, the additive comprises a nitrogen-containing cationic polymer.

[0105] In one embodiment of the present invention, the nitrogen-containing cationic polymer is the reaction product of a diamine having formula (I) and an epoxide having formula (III):

[0106]

[0107] in

[0108] R 1 , R 2 , R 3 and R 4 are independently H or C1-C3 alkyl;

[0109] A is a divalent linking group selected from the following: C2-C8 alkylene, C5-C 10 Cycloalkylene, phenylene and C6-C 20 Arylene, wherein A is optionally substituted with C1-C4 alkyl or OH;

[0110] Y is H or C1-C4 alkyl;

[0111] X is a halogen; and

[0112] p, q and r are each independently an integer from 0 to 10.

[0113] In another embodiment of the present invention, the nitrogen-containing cationic polymer is the reaction product of a diamine having formula (I) and a diepoxide having formula (IV):

[0114]

[0115] in

[0116] R 1 , R 2 , R 3 and R 4 are independently H or C1-C3 alkyl;

[0117] R 9 and R 10 are independently H or C1-C4 alkyl;

[0118] R 11 is selected from C2-C8 alkylene and C5-C 10 A divalent linking group of cycloalkylene, wherein R 11 Optionally substituted with C1-C4 alkyl or OH;

[0119] A is a divalent linking group selected from the following: C2-C8 alkylene, C5-C 10 Cycloalkylene, phenylene and C6-C 20 Arylene, wherein A is optionally substituted with C1-C4 alkyl or OH;

[0120] p, q and r are each independently an integer from 0 to 10; and

[0121] n is an integer of 1 to 20.

[0122] In another embodiment of the present invention, the nitrogen-containing cationic polymer is the polymerization product of an imidazole having formula (II) and an epoxide having formula (III):

[0123]

[0124] in

[0125] R 5 is H or C1-C6 alkyl;

[0126] R 6 , R 7 and R 8Each of R is independently H or C1-C6 alkyl, and R 7 and R 8 optionally connected to each other to form a saturated ring;

[0127] Y is H or C1-C4 alkyl; and

[0128] X is halogen.

[0129] In yet another embodiment of the present invention, the nitrogen-containing cationic polymer is the polymerization product of an imidazole having formula (II) and a diepoxide having formula (IV):

[0130]

[0131] in

[0132] R 5 is H or C1-C6 alkyl;

[0133] R 6 , R 7 and R 8 Each of R is independently H or C1-C6 alkyl, and R 7 and R 8 optionally connected to each other to form a saturated ring;

[0134] R 9 and R 10 are independently H or C1-C4 alkyl;

[0135] R 11 is selected from C2-C8 alkylene and C5-C 10 A divalent linking group of cycloalkylene, wherein R 11 is optionally substituted with C1-C4 alkyl or OH; and

[0136] n is an integer of 1 to 20.

[0137] Generally speaking, the reaction product of the amine compound and the epoxy compound can have a weight average molecular weight (Mw) value in the range of 100 g / mole to 50,000 g / mole, typically 500 g / mole to 30,000 g / mole, preferably 1,000 g / mole to 10,000 g / mole, although other Mw values ​​can also be used.

[0138] In one embodiment of the present invention, the nitrogen-containing cationic polymer has a weight average molecular weight (Mw) of about 1,000 g / mole to about 10,000 g / mole.

[0139] Generally, the amount of the nitrogen-containing cationic polymer in the electrolytic solution is in the range of 0.1 ppm to 20.0 ppm, or 0.5 ppm to 15.0 ppm, or 1.0 ppm to 10.0 ppm, based on the total weight of the electrolytic solution.

[0140] In one embodiment of the present invention, the amount of the nitrogen-containing cationic polymer in the electrolytic solution is in the range of 0.1 ppm to 20.0 ppm, or 0.5 ppm to 15.0 ppm, or 1.0 ppm to 10.0 ppm, based on the total weight of the electrolytic solution.

[0141] The method for making the electrodeposited copper foil of the present invention can be operated in a wide range of electrolyte solution temperatures. The temperature of the electrolyte solution is generally between about 20°C and about 80°C, preferably between about 25°C and about 75°C, and more preferably between 30°C and about 70°C.

[0142] The method for making the electrodeposited copper foil of the present invention can also be operated by applying a wide range of currents. Electrodeposition can be carried out in the range of about 30A / dm 2 To about 100A / dm 2 When the electrodeposition current density is higher than 60A / dm 2 When the current density is 200 ℃ and 800 ℃, the production rate of the electrodeposited copper foil can reach about at least 0.25 μm / second, which meets the standard industrial production rate.

[0143] The third aspect of the present invention is to provide a surface-treated electrodeposited copper foil, which comprises or is made of the electrodeposited copper foil of the present invention.

[0144] There are various types of surface treatments to impart desired properties to the copper foil, depending on the specific application. The electrodeposited copper foil of the present invention may be subjected to conventional surface treatment steps, such as pickling, roughening (e.g., nodule plating), forming a heat-resistant layer, an anti-oxidation layer, and / or an adhesion-promoting layer, to obtain a surface-treated electrodeposited copper foil. The surface treatment steps described above may be applied to the matte surface, the glossy surface, or both surfaces of the electrodeposited copper foil.

[0145] It should be noted that any of the above surface treatment steps are not expected to impair the uniformity of the matte surface of the base ED copper foil. In other words, the UF value of the surface treated copper foil of the present invention is expected to have the same UF value as the base copper foil of the present invention, or even less than the UF value of the base copper foil of the present invention.

[0146] For example, it can be speculated that a surface treatment step such as roughening by electroplating nodules on the matte surface and / or the glossy surface will form a nodule layer 4 having a thickness ranging from 100 nm to 1 μm. In addition, nodules plated on the matte surface may deposit more on the valleys than on the peaks, or vice versa, and therefore, the average thickness of the ED copper foil may change after the roughening step.

[0147] Please refer to Figure 2 A, which shows a cross-sectional view of a copper foil according to one embodiment of the present invention. Figure 2 In A, the base foil 1 has a matte surface and a smooth surface, and a plurality of protrusions are located on the matte surface. The peak height P1 is the distance as indicated by the dotted line 2; the valley height V1 is the distance as indicated by the dotted line 3. P1 to P5 refer to the five peak heights on the matte surface, and V1 to V5 refer to the five valley heights on the matte surface. The average thickness (T 平均 ) is calculated by adding the average peak height of P1 to P5 and the average valley height of V1 to V5, and then dividing by 2. The nodule layer 4 includes a plurality of nodules formed on the glossy surface of the base foil 1 .

[0148] It is worth noting that when roughening is performed on the matte surface of the copper foil according to one embodiment of the present invention, Figure 2 As shown in FIG. 1B , the nodule layer 4 comprises a plurality of nodules typically formed on peaks on the matte surface of the base foil 1. In addition, the nodule layer 4 on the matte surface or the glossy surface can be distinguished from the base foil 1 by SEM. Therefore, the average thickness of the surface treated ED Cu foil of the present invention will remain the same as the average thickness of the untreated base foil 1.

[0149] As previously described, after polishing off about 1 μm of the shiny surface of the ED copper foil, the surface area of ​​protrusions on the matte surface with flattened peaks having a surface area of ​​50 μm or more was counted and measured. 50+ After polishing, the peaks of the abnormally larger and higher protrusions and the nodules deposited thereon are also flattened. 最大 and PA 50+ / 1mm 2 The matte surface is also expected to be about the same as that of the untreated base foil 1. Therefore, the UF values ​​of the ED copper foils of the present invention are expected to be about the same after the surface treatment step.

[0150] The fourth aspect of the present invention is to provide products, which contain or are made of the electrodeposited copper foil of the present invention, including negative electrode collectors of lithium ion batteries, copper-clad laminates, flexible copper-clad laminates, heat sinks or printed circuit boards.

[0151] Without further elaboration, it is believed that one skilled in the art can utilize the present invention to its fullest extent using the preceding description.Therefore, the following examples should be construed as merely illustrative, and not limiting the present invention in any way.

[0152] Examples

[0153] The abbreviation "E" stands for "Example", and "CE" stands for "Comparative Example". The Examples and Comparative Examples were prepared in a similar manner except that different corresponding electrolytic solutions were used. The performance tests of the Examples and Comparative Examples were conducted in the same or similar manner.

[0154] Material

[0155] Gelatin was purchased from Jellice Pioneer Private Limited (Singapore), Taiwan Branch, model FL-FCC0.

[0156] Sodium bis(sulfopropyl) disulfide (SPS) was purchased from HOPAX International.

[0157] Hydroxyethyl cellulose (HEC) was purchased from DAICEL.

[0158] NCP-A: having formula (I) The diamine having formula (IV) The reaction product of a diepoxide of 1,000 to 10,000 g / mol is manufactured by DuPont Electronics, Inc. of Wilmington, Delaware, USA (hereinafter referred to as "DuPont Electronics") under the trade name Copper Gleam TM ,T1 for sale.

[0159] NCP-B: having formula (II) The imidazole and the imidazole having the formula (III) The reaction product of the epoxide of the present invention has a Mw of about 1,000-10,000 g / mol and is marketed by DuPont Electronics under the trade name Copper Gleam TM ,T2 for sale.

[0160] NCP-C: having formula (II) The imidazole has the formula (IV) The reaction product of the diepoxide of the present invention has a Mw of about 1,000-10,000 g / mol and is marketed by DuPont Electronics under the trade name CopperGleam TM ,T3 for sale.

[0161] Copper sulfate, sulfuric acid, hydrochloric acid, and commercial compounds of unknown origin were purchased from Sigma-Aldrich Company.

[0162] Preparation of Examples 1-13 and Comparative Examples 1-7

[0163] The ED copper foils of Examples 1-13 and Comparative Examples 1-7 were prepared by the following steps.

[0164] First, the electrolytic solution of each example or comparative example was prepared by thoroughly mixing copper sulfate (260 g / L), sulfuric acid (105 g / L), chloride ions and the one or more additives in the amounts shown in Table 1. Electrodeposition was carried out in an apparatus containing a titanium drum to be used as a negative electrode (cathode) and a dimensionally stable anode (IrO2 / Ti) to be used as a positive electrode. A DC power supply was used and the current density was set to 60 A / dm 2 . The space between the cathode and the anode was filled with the corresponding electrolytic solution, and the temperature of the electrolytic solution was maintained at 60°C. The copper foil of each example or comparative example was directly formed on the surface of the titanium roller for the plating duration specified in Table 1. Finally, the copper foil was removed from the titanium roller, and an electrodeposited copper foil was obtained. The copper foil samples of E1-E13 and CE1-CE7 were basic copper foils, which means that they were not subjected to any surface treatment step.

[0165] Table 1

[0166]

[0167]

[0168] Measurement method

[0169] The uniformity of the copper foils of Examples 1-13 and Comparative Examples 1-7 was measured by the following method when applicable.

[0170] 1. Peak, valley and average thickness (T 平均 )

[0171] The copper foil obtained in each example or comparative example was cut into a specimen (size: 2 cm×1 cm) for thickness measurement by SEM. For ease of handling, each specimen was immersed in a room temperature curable epoxy resin to obtain a Cu foil specimen coated with a transparent epoxy resin. It should be noted that the epoxy coating of the copper foil specimen is not visible or detectable by SEM.

[0172] The scanning electron microscope (model: JEOL IT300HR, IT800SHL) was set with a backscattered electron detector, enhanced contrast, reduced brightness, and a scanning speed longer than 40 s to obtain high-quality electron channel contrast images. The heights of 5 different peaks and 5 different valleys of each foil sample were recorded and averaged in Tables 2-1 and 2-2 below. Average thickness (T 平均 ) is calculated by adding the average peak height and the average valley height and then dividing by 2, and is also listed in Table 2-2.

[0173] Table 2-1

[0174]

[0175]

[0176] Table 2-2

[0177]

[0178]

[0179] 2. Maximum surface area of ​​the protrusion with a flat surface after polishing (A 最大 ) and 50 μm on the matte side 2 The number of protrusions with a flat surface after polishing (P 50+ )

[0180] A piece of copper foil sample of each example or comparative example is cut into a square of 10 cm×10 cm. Then, the sample is placed on a glass plate with the matte surface facing down and in contact with the glass plate. The glossy surface of the sample is polished by using SiC sandpaper #P1200 manufactured by Buehler company. After polishing off about 1 μm of the glossy surface, a flattening peak of the higher / larger protrusions on the matte surface of the sample appears. A photograph of the matte surface of each sample is taken by an optical microscope (STM7-CS100 from OLYMPUS) equipped with a 5x objective lens and a 10x eyepiece. The observation area of ​​each photo is 5,892,250 μm 2 .

[0181] The photo of each copper foil sample was analyzed by software to measure the surface area of ​​each protrusion with a flattened peak in the photo and count the number of protrusions with a 50 μm 2 or greater surface area flattened peaks (PA 50+ ). For comparison purposes, every 5,892,250 μm 2The number of counts of the above-mentioned protrusions observed for the matte surface area is divided by 5.892 to provide the number of counts per 1 mm 2 (i.e., 1,000,000 μm 2 ) PA with matte surface 50+ .

[0182] As mentioned previously, the uniformity factor (UF) of the matte surface of each Example and Comparative Example was calculated as follows:

[0183] UF=A 最大 / T 平均 (Equation 1)

[0184] Among them A 最大 : the maximum surface area of ​​protrusions on the matte surface having flattened peaks after polishing; and

[0185] T 平均 :Average thickness of ED copper foil (T 平均 ).

[0186] The measured and calculated data for each copper foil sample are listed in Table 3.

[0187] Table 3

[0188]

[0189]

[0190] As shown in Tables 1-3, the electrodeposited copper foils of Examples 1-13 of the present invention each have a uniform matte surface, as indicated by the UF value of 5.5 μm or less and the PA 50+ / 1mm 2 The addition of nitrogen-containing cationic polymers (including NCP-A, NCP-B and / or NCP-C) in the electrolytic solution unexpectedly enhances the matte surface uniformity of ED copper foil of E1-13 having a thickness ranging from about 69 μm to about 374 μm, regardless of the presence of gelatin or HEC.

[0191] In contrast, Comparative Examples 1-7 were prepared by using only conventional additives (such as gelatin and / or HEC) in an amount similar to the amount of nitrogen-containing cationic polymer in the corresponding electrolytic solution, and the resulting copper foils had poor uniformity, as judged by the corresponding UF values ​​(i.e., greater than 5.5 μm). In addition, the matte surface of each copper foil sample of CE1-7 had a PA ranging from 9.0 to 25.6. 50+ / 1mm 2 Matte surface.

[0192] Figure 3A shows a SEM cross-sectional image of a copper foil sample of CE3 with a poorly uniform matte surface, where UF is 7.85 μm and PA 50+ / 1mm 2 9.0 for matte finish. Figure 3 B shows a SEM cross-sectional image of a copper foil sample of E9 with a uniform matte surface, where UF is 1.65 μm and PA 50+ / 1mm 2 1.7 for matte surfaces.

[0193] Therefore, when the copper foil thickness is between about 30 μm and about 400 μm, the method of the present invention effectively suppresses the growth of abnormally higher and larger protrusions on the matte surface of the ED copper foil during electrodeposition. PCBs made of copper-clad laminates or flexible copper-clad laminates containing the ED Cu foil of the present invention are expected to have improved safety and reliability, and fewer undesirable etching and / or short circuit problems.

[0194] Although specific embodiments of the present invention have been shown and described, further modifications and improvements will occur to those skilled in the art. Therefore, it is to be understood that the present invention is not limited to the specific forms shown, and in the appended claims below, all modifications that do not depart from the spirit and scope of the present invention are intended to be covered.

Claims

1. An electrodeposited copper foil, characterized in that: The electrodeposited copper foil has an average thickness (T 平均 ); The electrodeposited copper foil has a matte surface and a glossy surface; The matte surface of the electrodeposited copper foil comprises a plurality of protrusions; and Every 1mm 2 The matte surface has a 50 μm 2 The number of protrusions on the matte surface having flattened peaks after polishing of a surface area of ​​or greater (PA 50+ ) is 8.0 or less; in The average thickness is measured by scanning electron microscopy (SEM); Peaks of some protrusions on the matte surface were flattened by: a) placing the electrodeposited copper foil on a glass substrate, wherein the matte surface was in contact with the glass substrate, and b) polishing away about 1 μm of the glossy surface of the electrodeposited copper foil by using silicon carbide sandpaper having a grit size of 1200; The number and surface area of ​​the protrusions on the matte surface having flattened peaks after polishing are counted and measured by using an optical microscope having a magnification of 50 times or more and a resolution of at least 0.1 μm.

2. The electrodeposited copper foil according to claim 1, wherein: The matte surface of the electrodeposited copper foil has a PA of 6.0 or less 50+ / 1mm 2 The matte surface.

3. The electrodeposited copper foil according to claim 1, wherein: The matte surface of the electrodeposited copper foil has a uniformity factor (UF) of 5.5 μm or less, and the UF is calculated according to the following Equation 1: UF=A 最大 / T 平均 (Equation 1) Among them A 最大 is the maximum surface area (A) of the protrusions on the matte surface having flattened peaks after polishing 最大 );and T 平均 is the average thickness of the electrodeposited copper foil.

4. The electrodeposited copper foil according to claim 1, wherein: The matte surface of the electrodeposited copper foil has a UF of 4.0 μm or less.

5. A method for manufacturing the electrodeposited copper foil according to claim 1, the method comprising: i) providing an electrolytic solution in an electrolytic cell; ii) applying a current of a certain current density to the anode plate and the rotating cathode drum spaced apart from each other in the electrolytic solution; iii) electrodepositing copper foil on the rotating cathode drum; as well as iv) separating the copper foil formed in step iii) to obtain an electrodeposited copper foil; in The electrodeposited copper foil has an average thickness of about 30 μm to about 400 μm; The electrodeposition in step iii) is carried out at about 30 A / dm 2 To about 100A / dm 2 The current density is 2.14V. The electrolytic solution comprises: From about 120 g / L to about 450 g / L of copper sulfate; From about 30 g / L to about 140 g / L of sulfuric acid; From about 0.1 ppm to about 60 ppm of chloride ion; and From about 0.1 ppm to about 50 ppm of additives.

6. The method of claim 5, wherein: The electrodeposition of step iii) is performed at a temperature of the electrolytic solution of about 20°C to about 80°C.

7. The method of claim 5, wherein: The additive in the electrolytic solution includes gelatin, animal glue, cellulose, organic sulfonic acid or its salt, nitrogen-containing cationic polymer, or a mixture thereof.

8. The method of claim 7, wherein: The additive includes a nitrogen-containing cationic polymer, and the nitrogen-containing cationic polymer has a weight average molecular weight of about 1,000 to about 10,000 g / mole.

9. The method of claim 8, wherein: The nitrogen-containing cationic polymer is the reaction product of a diamine having formula (I) or an imidazole having formula (II) and an epoxide having formula (III) or a diepoxide having formula (IV): in R 1 , R 2 , R 3 and R 4 are independently H or C1-C3 alkyl; R 5 is H or C1-C6 alkyl; R 6 , R 7 , R 8 Each of R is independently H or C1-C6 alkyl, and R 7 and R 8 optionally connected to each other to form a saturated ring; R 9 and R 10 are independently H or C1-C4 alkyl; R 11 is selected from C2-C8 alkylene and C5-C 10 A divalent linking group of cycloalkylene, wherein R 11 Optionally substituted with C1-C4 alkyl or OH; A is a divalent linking group selected from the following: C2-C8 alkylene, C5-C 10 Cycloalkylene, phenylene and C6-C 20 Arylene, wherein A is optionally substituted with C1-C4 alkyl or OH; Y is H or C1-C4 alkyl; X is a halogen; p, q and r are each independently an integer from 0 to 10; and n is an integer of 1 to 20.

10. A surface-treated electrodeposited copper foil, comprising the electrodeposited copper foil according to claim 1, said electrodeposited copper foil having a surface of said electrodeposited copper foil to which at least one surface treatment step has been applied.

11. The surface-treated electrodeposited copper foil according to claim 10, wherein: The surface treatment step includes an acid washing step, a roughening step, a heat-resistant layer forming step, an antioxidant layer forming step, or an adhesion-promoting layer forming step. 12 . An article, wherein the article comprises the electrodeposited copper foil according to claim 1 or the surface-treated electrodeposited copper foil according to claim 10 .

13. The article of claim 12, wherein: The product is a negative electrode collector of a lithium ion battery, a copper-clad laminate, a flexible copper-clad laminate, a heat sink, or a printed circuit board.

Citation Information

Patent Citations

  • Copper plating bath and plating method for substrate using the copper plating bath

    US6800188B2

  • Plating method

    US7374652B2

  • Leveler compounds

    US7662981B2

  • Plating bath and method

    US8268158B2